COMPARATIVE PERFORMANCE EVALUATION OF INTANGIBLE FACTORS FOR ECONOMIC DEVELOPMENT OF MOSCOW REGION AND THE KRASNODAR TERRITORY - A. Yaroshchuk; A. Nazarov (Вестник университета, 2017)
The article examines the effect of potential intangible assets for the effective development of the regional economy on the example of Moscow region and the Krasnodar territory, the comparative characteristics of their practical use.